Substitution of waqf in Terengganu: maqasid shariah and public interest approach - Awang, Abdul Bari; Awang Abd. Rahman @ Jusoh, Amilah; Amir Hamzah, Faiz Sakinah (2018)
Abstract. Application of waqf property in modern society is highly anticipated to fulfill more demand for economic growth and development and help the needs in society. Therefore, Istibdal Waqf is indispensable in the implementation of waqf so the waqf property will not be wasted and always beneficial to society. Although the Istibdal Waqf is important but it is doubtful whether it is a necessity (Daruriyyat) for the society or needs (Hajiyyat) or embellishment (Tahsiniyyat) while the discussion are involve in the framework of Maqasid Shariah so the main purpose of waqf are still preserved. This article aims at discussing the issues with regard to the application of Istibdal Waqf concept in Islam. Specifically, the study sets out to explain on the importance of Istibdal Waqf for muslim society in the framework of maqasid shariah and public interest. The study also focusing on Istibdal inTerengganu as case study